2023
DOI: 10.1088/1755-1315/1168/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Testing Using Boundary Value Analysis Methods for Geographic Information System

Abstract: Perusahaan Daerah Perkebunan (PDP) Kahyangan is a Regional Owned Enterprise (BUMD) in Jember. It was formed to realize the welfare of the community. Based on interviews, PDP’s given profit contribution has declined in recent years due to the absence of good management of its potential. As a result of the challenges, it can be determined that PDP Jember requires a management system that can assist in acquiring data on the distribution of plantation and forestry land commodities in Jember, as well as mapping exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Research has shown the importance of using techniques such as Boundary Value Analysis in testing web-based applications to ensure their functionality and reliability (Prayudha et al, 2020). By using Black Box Testing and Boundary Value Analysis techniques, developers can identify potential problems at the boundaries of valid input ranges, significantly improving web application quality and robustness (Puspitasari et al, 2023). Other research also shows that Boundary Value Analysis (BVA) is proven to be the most effective compared to other techniques, such as Equivalence Partitioning (EP) and random testing (Reid, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown the importance of using techniques such as Boundary Value Analysis in testing web-based applications to ensure their functionality and reliability (Prayudha et al, 2020). By using Black Box Testing and Boundary Value Analysis techniques, developers can identify potential problems at the boundaries of valid input ranges, significantly improving web application quality and robustness (Puspitasari et al, 2023). Other research also shows that Boundary Value Analysis (BVA) is proven to be the most effective compared to other techniques, such as Equivalence Partitioning (EP) and random testing (Reid, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The objective is to detect any software defects that may manifest at these interface boundaries. The above citations provide examples of scholarly articles that examine the topic of Boundary Value Analysis [21]. User Acceptance Testing (UAT) is a critical phase in the software development process.…”
Section: Testingmentioning
confidence: 99%